Understanding and exploiting plant beneficial microbes - Finkel, Omri M; Castrillo, Gabriel; Herrera Paredes, Sur; Salas González, Isai; Dangl, Jeffery L (Current opinion in plant biology, 2017)
•Soil microbiomes induce reproducible plant phenotypes.•Large collections of plant-associated microbes are available for research.•Plant growth promoting microbial inoculants can persist in soil for weeks.•Co-regulation of immune system function and nutritional stress responses exists.•Deployment of consortia may enable more resilient plant phenotypes than single strains. After a century of incremental research, technological advances, coupled with a need for sustainable crop yield increases, have reinvigorated the study of beneficial plant–microbe interactions with attention focused on how microbiomes alter plant phenotypes. We review recent advances in plant microbiome research, and describe potential applications for increasing crop productivity. The phylogenetic diversity of plant microbiomes is increasingly well characterized, and their functional diversity is becoming more accessible. Large culture collections are available for controlled experimentation, with more to come. Genetic resources are being brought to bear on questions of microbiome function. We expect that microbial amendments of varying complexities will expose rules governing beneficial plant–microbe interactions contributing to plant growth promotion and disease resistance, enabling more sustainable agriculture.